Nephrologist, Pulmonologist Connection: From Bench to Bedside, Mini Review (Iranian Journal of Kidney Diseases, 2020)
Whether working in intensive care unit or not as nephrologists we are all facing complicated cases with different sign and symptoms. Among them is a category of patients presenting with concomitant respiratory and kidney failure called pulmonary renal syndrome, which needs mutual connection between nephrologist and pulmonologist closely for the best decision-making. Although this is not a common entity, still associated with high rate of morbidity and mortality involving diffuse alveolar hemorrhage and glomerulonephritis. Understanding the updates in the field of management would benefit both the patients and caregivers providing clear answers to present obstacles.